2010
DOI: 10.1111/j.1439-0396.2009.00983.x
|View full text |Cite
|
Sign up to set email alerts
|

ORIGINAL ARTICLE: Seasonal quality profile and production of foliage from trees grown on degraded cropland in arid Uzbekistan, Central Asia

Abstract: Feed shortages hamper livestock rearing and thus impede the development of rural livelihoods in Central Asia. The production and in vitro quality of foliage from Ulmus pumila, Elaeagnus angustifolia and Populus euphratica on degraded cropland were examined to determine the potential of these species to supplement diary cattle diets. Leaf dry matter (DM) production of the species, respectively, averaged 6, 8 and 17 t DM/ha, 4 years after planting. Over seasons and years, crude protein concentrations (g/kg DM) r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…Its CP content is however, above the threshold of 60 g/kg DM required by the microbes in the rumen to support metabolic functions of their host (Van Soest, 1994). The CP content across seasons for all MPTS investigated was adequate to support meat and milk production of ruminant animals (Lamers and Khamzina, 2010). They may therefore serve as ready source of year‐round cheap protein supplements for herds of resource‐poor farmers in Sub‐Saharan Africa and thereby help to improve the quality of feed and at the same time reduce the cost of production.…”
Section: Discussionmentioning
confidence: 99%
“…Its CP content is however, above the threshold of 60 g/kg DM required by the microbes in the rumen to support metabolic functions of their host (Van Soest, 1994). The CP content across seasons for all MPTS investigated was adequate to support meat and milk production of ruminant animals (Lamers and Khamzina, 2010). They may therefore serve as ready source of year‐round cheap protein supplements for herds of resource‐poor farmers in Sub‐Saharan Africa and thereby help to improve the quality of feed and at the same time reduce the cost of production.…”
Section: Discussionmentioning
confidence: 99%
“…Lamers and Khamzina [23] studied the quality profile and production of foliage from trees grown on degraded croplands of Central Asia and found that the leaves of E. angustifolia could be used to supplement protein poor feed rations on dairy cows. The values of feed analysis that they obtained were like authors', considering that they worked on young (4 years old) trees that have not yet begun the reproductive face [6].…”
Section: Resultsmentioning
confidence: 99%
“…Also, because of the notorious shortage in feed supply, which presently causes poor livestock productivity in Uzbekistan (Djumaeva et al, 2009), raising cattle under these conditions needs better feed diets. With high foliar crude protein (CP) contents and a nutritive value of tree leaves that is somewhat comparable to alfalfa, a common feed in the region (Lamers and Khamzina, 2010), tree leaves can complement and improve the presently low-quality diet of livestock. The SPAD-502 can be used to monitor leaf CP content during the growing season, since the N content of CP, one of the major feed quality indicators, is 16% (Close and Menke, 1986).…”
Section: Discussion and Options For Actionmentioning
confidence: 99%